PERUBAHAN MORFOLOGI UMBI KENTANG KONSUMSI (Solanum tuberosum L. Var Granola) SETELAH PERLAKUAN CARA DAN WAKTU PENYIMPANAN YANG BERBEDA - Edi Purnomo; Sri Widodo Agung Suedy; Sri Hariyati (Jurnal Akademika Biologi, 2014)
Agriculture product storage is an important that must be done in post harvest handling. Potato is one of the easily broken product, so that a good handling is needed to mantain quality as one of functional food. The present study aims to know the effects of methode and time storage of morphology tuber potato consumption. This  research  uses Completely Randomize Design on  factorial pattern with  two  factors.  First, method storage (K1); saved in open container, (K2); saved in close container. Second, time storage (T1); 2 weeks, (T2); 4 weeks, (T3);  6 weeks, (T4); 8 weeks, (T5); 10 weeks. This research uses 10 treatments and 3 replications. The parameter includes morphology quantitatively: diameter decreasing, total black spot, percentage of breakage and morphology qualytatively: surface alteration and bud. Data were analyzed using  ANOVA, followed by Duncan’s test at the significance level of 95%. The results showed that storage method in open container (K1) tends increase diameter shrinkage. Storage time caused alteration of morphology in quantitative and qualytative. Interaction between method and time of storage influence in total black spot (p<0,05). Storage of potato tuber consumption had better kept at a distance from light presence less 4 weeks. Keywords: storagemethod, storagetime, Solanum tuberosum L., morphology